Effect of Differences in Fluid Pressure Passing Through Venturi on Dissolved Oxygen Level in Medical Waste Water: Effect of Differences in Fluid Pressure Passing Through Venturi on Dissolved Oxygen Level in Medical Waste Water - Anwar, Zainuri; Irfan Dzaky, Muhammad; Reco Putra, Aldony; Bayu Saputra, Fajri; Roihan, Mohammad; Audhi Natanegara, Muhammad Audhi Natanegara (UIR PRESS, 2026)
Medical wastewater is characterized by a high organic load, which has the potential to deplete Dissolved Oxygen (DO) levels in receiving waters. One effective method to mechanically increase DO levels is through the aeration process using a venturi injector-based microbubble generator (MBG). This study aims to analyze the effect of fluid pressure variations passing through the venturi on the increase of DO levels in medical wastewater. The research was conducted experimentally by varying the fluid input pressures at 1 bar, 2 bar, 3 bar, and 4 bar to observe the effectiveness of ambient air suction through the venturi injection. DO level measurements were carried out over a time range of 15–60 minutes using a DO meter. The results indicated an increase in DO levels at an inlet pressure of 3 bar, reaching approximately 9 mg/L. However, a decrease in DO levels occurred at 4 bar, dropping to 6.1 mg/L. This was due to excessive velocity causing turbulence in the divergent zone, so the bubbles to collide and coalesce